Single quantum emitter spectroscopy with visible sub-10 fs pulses - Weigel, A; Sebesta, A; Kukura, P (Optical Society of American (OSA), 2014)
We present a novel white light source providing sub-10 fs visible pulses with MHz repetition rates and apply it in femtosecond pulse pair experiments on single quantum emitters. © 2014 OSA.